1999
DOI: 10.21273/jashs.124.4.430
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of `Genesis' Triploid Watermelon following Mechanical Scarification

Abstract: ADDITIONAL INDEX WORDS. Citrullus lanatus, seedless watermelon, seedlings, seedcoat adherence ABSTRACT. Production of triploid watermelon [Citrullus lanatus (Thunb.) Matsum & Nakai] transplants is hindered by poor, inconsistent emergence, and frequent seed coat adherence to cotyledons. Seed coat adherence leads to weakened and slow growing plants. High seed costs, coupled with stand establishment problems, discourages transplant producers from growing this crop. Improvement of triploid watermelon emergence wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Splitting the seedcoat of tetraploid watermelons laterally improved germination (Nerson et al, 1985). Recently, Duval and NeSmith (1999) confirmed that mechanical scarification improved and increased the consistency of emergence of 'Genesis' triploid watermelon; however, emergence was still not at an acceptable level. Alternative mechanical pretreatments, with or without chemical treatment, of triploid watermelon seed could improve germination and stand establishment.…”
mentioning
confidence: 97%
“…Splitting the seedcoat of tetraploid watermelons laterally improved germination (Nerson et al, 1985). Recently, Duval and NeSmith (1999) confirmed that mechanical scarification improved and increased the consistency of emergence of 'Genesis' triploid watermelon; however, emergence was still not at an acceptable level. Alternative mechanical pretreatments, with or without chemical treatment, of triploid watermelon seed could improve germination and stand establishment.…”
mentioning
confidence: 97%
“…Genesis was improved when seeds were clipped, with the greatest improvement when the seedcoat was completely removed. Duval and NeSmith (1999) also reported that scarified seed germinated more uniformly than did nonscarified seeds. Nerson et al (1985) found that lateral splitting of seeds did not improve germination in diploids, but increased in tetraploids.…”
Section: Resultsmentioning
confidence: 92%
“…Seed scarification, another germination promoting method used for pelleted pine seeds, involves intentional damage to the impervious seed coat, enabling more rapid and even water uptake and gas exchange to the embryo [5]. Germination is also controlled by plant growth regulators such as auxins and gibberellins.…”
Section: Introductionmentioning
confidence: 99%